Development of a mobile application for items exchange - Ramanathan Rajaraj (Nanyang Technological University, 2023)
This project aims to develop a mobile application, specifically for the Android Operating System (OS). The development of the mobile application is aimed at creating a platform for users to exchange items they no longer need or use. The application has been named WExchange. With the increasing concern about environmental issues, being environmentally friendly and sustainable has gained importance around the world. WExchange enables users to exchange items that they no longer need with others, reducing waste and promoting a more sustainable lifestyle. The application is developed using Android Studio and Java programming language. Google Firebase is used as the database for the application. WExchange allows users to create an account for themselves, list items to exchange, and look through items listed by other users. Users can then carry out a purely item-for-item exchange deal via the application. The items to be exchanged between the two users will be completely up to their discretion.